Aberrant peak lactate response in MS - Schlüter, Kathrin (NeuroRehabilitation, 2017)
BACKGROUND: The peak blood lactate response to an exhaustive exercise test in a number of chronic conditions has been shown to differ from that seen in healthy, untrained individuals. However, this has not been investigated for patients with multiple sclerosis (MS). OBJECTIVE: The main objective was to determine and compare the peak blood lactate response to exercise and the maximal workload between two groups of MS patients with different illness severity. METHODS: Twenty-five patients with a relapsing-remitting disease course (Group RR) and 41 patients with a secondary- or primary chronic progressive disease course (group CP) performed an exhaustive incremental bicycle ergometry. Peak blood lactate, maximal workload, peak oxygen consumption and maximal heart rate were measured. RESULTS: The peak blood lactate levels and maximal workload differed significantly between the groups (group CP<group RR; p<0.001). Furthermore spiroergometric peak performance markers in both groups were significantly lower than predicted for healthy age and sex matched untrained groups. CONCLUSION: A reduced peak blood lactate response to exercise is a novel finding for MS patients. This calls into doubt if the lactate performance tests and lactate thresholds used for healthy individuals can be transferred to MS patients.